On the Anomalously Strong Dependence of the Acoustic Velocity of Alumina on Temperature in Aluminosilicate Glass Optical Fibers—Part I: Material Modeling and Experimental Validation. (26th August 2015) - Dragic, Peter D.; Martin, Steve W.; Ballato, Arthur; Ballato, John
Abstract : The thermo‐acoustic coefficient (TAC, or the change of acoustic velocity with a change in temperature) of the alumina (Al2 O3 ) component in aluminosilicate core silica clad glass optical fibers is anomalously large. It has been speculated previously that this anomaly is not due to a large alumina TAC, but instead due to the thermal expansion mismatch between the aluminosilicate core glass and the pure silica cladding glass. In this new work, it is shown that the acoustic velocity of the aluminosilicate core glass changes much differently than that for a bulk aluminosilicate glass. In the high alumina content compositional range, it is found that the larger core‐region thermal expansion results in a net positive pressure imparted on the silica component in the core. As the acoustic velocity of silica has a strong negative dependence on any applied pressure, this offsets the bulk positive‐valued thermal response of silica. Utilizing a modified form of the Winkelmann–Schott additivity model, the effect of the thermal expansion mismatch between the core and clad glasses is incorporated, and the resultant TAC determined for alumina is fully consistent with data found in the literature for bulk alumina. The consideration and incorporation of the thermal expansion of the core and clad glasses adds another degree of freedom to the design of specialty optical fibers for distributed sensor applications. Complementary to this article, Part II describes an efficient computational route for determining selected physical properties of an amorphous analog to a given crystalline form whose physical properties are known.